Die Geostiba-Arten des Fernen Ostens Russlands (Coleoptera, Staphylinidae, Aleocharinae) Beiträge zur Kenntnis ostpaläarktischer Insekten (10). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The Geostiba fauna of the Russian Far East consists of three species, for which a diagnostic key is presented. Geostiba (Ditroposipalia) kusnetzovi sp. n. [Khabarovskiy Kray: Boytsovo N Bikin] is described and compared with the species from the Russian Far East. The genitalia of the new species and the previously unknown spermatheca of Geostiba vladivostokensis Pace, 1997 are figured. Geostiba sakhalinensis Pace, 1997 is widely distributed on the island Sakhalin and in the Sikhote-Alin mountain range. Geostiba vladivostokensis Pace, 1997 and Geostiba rougemonti Pace, 1993 are transferred from the subgenus Indatheta Cameron, 1939 to the subgenus Sipalotricha Scheerpeltz, 1931. Nomenclatural Acts kusnetzovi Zerche, 2000 (Geostiba (Ditroposipalia)), spec. n.